Clinical Manifestations and Prognosis Factors in Severe Cutaneous Adverse Drug Reaction (Scadr) - Oktavriana, Triasari; Lauda, Benedikta; Putri, Osdatilla Esa (Jurnal Health Sains, 2025)
Severe Cutaneous adverse drug reaction (SCADR) is a severe skin reaction due to the use of drugs that can be life-threatening. This article describes the clinical manifestations and prognosis factors that affect SCADR patients. The most common types of SCADR were Stevens-Johnson Syndrome (SSJ) and Toxic Epidermal Necrolysis (TEN). The drugs that most often trigger are antibiotics and anticonvulsants. The main clinical manifestations include erythematosa skin lesions, epidermal necrolysis, and mucosal involvement. Significant prognosis factors include the extent of the affected skin area, internal organ involvement, and SCORTEN score. Patients with high SCORTEN scores have a greater risk of mortality. Early treatment and discontinuation of trigger drugs are key factors in improving clinical outcomes. The conclusion is early recognition of clinical manifestations of SCADR as well as assessment of prognosis factors can be helpful in patient management and reduce the risk of serious complications. The study also highlights the importance of educating medical personnel in detecting and managing severe drug reactions.